Epidemiological and clinical aspects of scorpionism by Tityus trivittatus in Argentina - de Roodt, Adolfo R. (2003)
Fil: de Roodt, Adolfo R. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Producción de Biológicos; Argentina.